Masked high progesterone levels during in vitro fertilization and embryo transfer treatment in a patient with 21‐hydroxylase deficiency: A case report. Issue 5 (1st March 2021) - Mizusawa, Yuri; Katayama, Kazuaki; Matsumoto, Yukiko; Kokeguchi, Shoji; Shiotani, Masahide
Abstract: The most common form of congenital adrenal hyperplasia is 21‐hydroxylase deficiency (21OHD). Women with 21OHD have reduced fertility because of excessive production of adrenal androgen and progesterone, which can inhibit folliculogenesis, disturb the normal gonadotropin secretion pattern and development of the endometrium, and affect endometrial receptivity. Here, we report on an infertile woman with 21OHD who initially showed normal progesterone levels and spontaneous ovulation with the treatment by an endocrinologist. However, in vitro fertilization and embryo transfer repeatedly failed because of a gradual elevation in progesterone, which was masked by fertility treatment. The case underlines that close coordination is required between the endocrinologist and reproductive specialist for the total treatment for woman with 21OHD.